Fenomena Generasi Strawberry Pada Mahasiswa di FISIP - Amalia, Dina; Damaiyanti, Varinia Pura (CV. ITTC INDONESIA, 2024)
Entering the modern era and the rapid pace of technology, mental health has become an important issue that must be paid attention to, especially for teenagers and adults who are currently known to tend to experience excessive stress, anxiety and depression. Mental health issues are closely related to the strawberry generation, which is considered to have a soul that is more vulnerable and sensitive to pressure from the social environment, family and social media than previous generations. The pressure they experience makes them a generation that has a higher level of awareness of mental health issues compared to previous generations, which leads to this happening self diagnose or self-identify without assistance from a medical professional. This research is aimed at understanding habits self diagnose among FISIP students at Lambung Mangkurat University (ULM) as the strawberry generation, with qualitative methods and phEnomEnological research types explored through George Herbert Mead's